Аналіз витоків даних у інформаційних системах - Задерейко, Олександр Владиславович; Трофименко, Олена Григорівна; Прокоп, Юлія Віталіївна; Логінова, Наталія Іванівна; Кухаренко, Сергій Вікторович (Київ : Державний науково-дослідний інститут МВС України, 2021)
У статті розглянуто питання забезпечення приватності користувачів інформаційних систем, представлених стаціонарними та мобільними пристроями комунікації. Показано, що наявна організація комунікації DNS трафіку інформаційної системи несе загрозу приватності користувача. Виконано фіксацію і аудит DNS трафіку пристроїв комунікації з цифровим простором. Установлено, що при виконанні блокування сторонніх з’єднань системного і прикладного програмного забезпечення пристроїв комунікації працездатність інформаційної системи не порушується. Визначено, що ідентифікація пристрою комунікації пов’язана із процесом збору інформації про апаратне та програмне забезпечення пристрою комунікації.

It was determined that such an organization of communication poses a threat to the privacy of users due to the possibility of access to the provider’s DNS server logs by authorized government services. Traffic was recorded for a typical user information system to identify ways of collecting data from stationary and mobile communication devices of users. An audit of outgoing and incoming connections of communication devices with digital space was carried out. It is determined that the system and application software of the communication device establishes connections with hosts that belong to IT companies providing services for the transit, collection, processing, and monetization of user data. The suggested criteria made it possible to unambiguously classify functional and third-party connections of the system and application software of communication devices. The operability of the system and application software of communication devices after blocking functional and third-party connections of the information system was experimentally tested. It was found that when blocking third-party connections, the operability of the information system is not impaired. The principles of constructing digital prints of a communication device are considered. It is shown that the process of building digital prints is based on the use of identification methods. The principles of an identification of communication devices in the digital space are analyzed. It has been established that the process of unambiguous identification of a communication device is inextricably linked with the collection of the maximum possible information about the hardware and software configuration of the communication device. Keywords: DNS query, DNS server, data leaks, DNS traffic, data leak analysis, communication device, device identification.
Аналіз витоків даних у інформаційних системах / О. В. Задерейко, О. Г. Трофименко, Ю. В. Прокоп, Н. І. Логінова, С. В. Кухаренко // Сучасна спеціальна техніка : науково-практичний журнал. - Київ : Державний науково-дослідний інститут МВС України, 2021. - № 3 (66). - С. 16-30.
Keywords: DNS запит; DNS сервер; витоки даних; DNS трафік; аналіз витоків даних; пристрій комунікації; ідентифікація пристроїв комунікації; DNS query; DNS server; data leaks; DNS traffic; data leak analysis; communication device; device identification